Ultimate field trip 3 : wading into marine biology - Goodman, Susan E., 1952-; Doolittle, Michael J. (New York : Aladdin Paperbacks, 2000)
A middle school class from Boston visits Cobscook Bay, Maine, to learn about the marine biology of the Bay's tidal zone.
Includes bibliographical references (p. [48]).
Book Links (A.L.A.).
Kirkus Review.
Wilson's Junior High School.
5.3.
5.3
Keywords: Marine biology -- Study and teaching (Elementary) -- Maine -- Cobscook Bay -- Juvenile literature; Tide pool ecology -- Study and teaching (Elementary) -- Maine -- Cobscook Bay -- Juvenile literature; Tide pools -- Study and teaching (Elementary) -- Maine -- Cobscook Bay -- Juvenile literature; Ecology; Marine biology; School field trips; Tide pool ecology; Tide pools; Ecology; Field trips; Marine biology; Tide pool ecology; Cobscook Bay (Me.); Cobscook Bay (Me.)